2017
DOI: 10.1021/acs.inorgchem.7b01828
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt- and Rhodium-Corrole-Triphenylphosphine Complexes Revisited: The Question of a Noninnocent Corrole

Abstract: A reinvestigation of cobalt-corrole-triphenylphosphine complexes has yielded an unexpectedly subtle picture of their electronic structures. UV-vis absorption spectroscopy, skeletal bond length alternations observed in X-ray structures, and broken-symmetry DFT (B3LYP) calculations suggest partial Co-corrole character for these complexes. The same probes applied to the analogous rhodium corroles evince no evidence of a noninnocent corrole. X-ray absorption spectroscopic studies showed that the Co K rising edge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 86 publications
4
50
0
Order By: Relevance
“…Recently, Nocera and Kar independently reported that several copper complexes of meso ‐aryl‐substituted corroles consist of the central copper(II) ion and the divalent corrole π‐radical ligand with strong antiferromagnetic interaction between the copper(II) and the π‐radical fragment, thereby behaving as an overall singlet spin‐state even at room temperature. Similar ligand non‐innocent behaviors have also been known for silver octabromocorroles, chloroiron and nitrosoiron corroles, triphenylphosphine cobalt corroles, and chloromanganese corroles . Another important observation is the metal‐ligand interaction depending on the size of the ligand.…”
Section: Introductionsupporting
confidence: 58%
“…Recently, Nocera and Kar independently reported that several copper complexes of meso ‐aryl‐substituted corroles consist of the central copper(II) ion and the divalent corrole π‐radical ligand with strong antiferromagnetic interaction between the copper(II) and the π‐radical fragment, thereby behaving as an overall singlet spin‐state even at room temperature. Similar ligand non‐innocent behaviors have also been known for silver octabromocorroles, chloroiron and nitrosoiron corroles, triphenylphosphine cobalt corroles, and chloromanganese corroles . Another important observation is the metal‐ligand interaction depending on the size of the ligand.…”
Section: Introductionsupporting
confidence: 58%
“…[11] Previous studies have shown that this level accurately reproduces geometries and energies of cobalt corrole complexes. [1c], …”
Section: Methodsmentioning
confidence: 99%
“…In recent years, metallocorroles have provided many examples of well-characterized noninnocent systems. [19][20][21][22] Key examples include MnCl, 23 FeCl, [9][10][11][12][13][14][15] FeNO, [24][25][26][27] Fe 2 (μ-O), 28 Copy 29 /DMSO 30 ( py = pyridine), Co-PPh 3 , 31 and Cu [32][33][34][35][36][37][38][39][40] corrole derivatives. It is worth noting that all these involve first-row transition metals.…”
Section: Introductionmentioning
confidence: 99%